Fiscal Space for Health in the Kyrgyz Republic - World Bank (World Bank, Washington, DC, 2019)
This report is organized into five chapters. Chapter one provides an estimate of the relative efficiency position of the Kyrgyz Republic based on its health outcomes and health expenditure. It is then analyzed to understand whether the sector is mostly in need of additional funding or needs to spend more effectively, or a combination of both. Chapter two derives the base fiscal space scenario: what the health sector can hope for given macroeconomic projections, expectations of external funding, and options to reprioritize health in the budget. These options do not require any specific action short of some active lobbying to drag more resources toward health over arguments that the country overall would gain by getting more. Chapter three examines potential new sources of funds through feasibly and sustainably raising new domestic revenues for health or sources of budgetary savings that will come from limiting financing responsibilities of the health sector. Reforms needed mostly involve the general government as they imply changes in taxes or benefits.